Social interactions affecting caste development through physiological actions in termites - Watanabe, Dai; Gotoh, Hiroki; Miura, Toru; Maekawa, Kiyoto (Frontiers in Physiology, 2014)
A colony of social insects is not only an aggregation of individuals but also a functional unit. To achieve adaptive social behavior in fluctuating environmental conditions, in addition to coordination of physiological status in each individual, the whole colony is coordinated by interactions among colony members. The study on the regulation of social-insect colonies is termed “social physiology”. Termites, a major group of social insects, exhibit many interesting phenomena related to social physiology, such as mechanisms of caste regulation in a colony. In their colonies, there are different types of individuals, i.e., castes, which show distinctive phenotypes specialized in specific colony tasks. Termite castes comprise reproductives, soldiers and workers, and the caste composition can be altered depending on circumstances. For the regulation of caste compositions, interactions among individuals, i.e. social interactions, are thought to be important. In this article, we review previous studies on the adaptive meanings and those on the proximate mechanisms of the caste regulation in termites, and try to understand those comprehensively in terms of social physiology. Firstly, we summarize classical studies on the social interactions. Secondly, previous studies on the pheromone substances that mediate the caste regulatory mechanisms are overviewed. Then, we discuss the roles of a physiological factor, juvenile hormone (JH) in the regulation of caste differentiation. Finally, we introduce the achievements of molecular studies on the animal sociality (i.e. sociogenomics) in terms of social physiology. By comparing the proximate mechanisms of social physiology in termites with those in hymenopterans, we try to get insights into the general principles of social physiology in social animals.